The impact of exchange rate volatility on Sri Lanka’s export growth - Francis, S.J.; Ganeshamoorthy, M. (University of Colombo, 2017)
Exchange rate volatility affects export competitiveness and, thereby, has an impact on export growth. Economies that embark on export-led economic growth endeavour to maintain a competitive exchange rate policy as an important measure of macroeconomic management. Many studies have investigated the impact of exchange rate volatility on export growth. Yet, only a few have found a significant relationship between these variables. This paper investigates the same issue in the context of Sri Lanka. It focuses on the causal effects of the short- and long-run relationship between exchange rate movements and export growth in Sri Lanka. It employs quarterly data spanning the first quarter of 2000 to the fourth quarter of 2015. It incorporates the following variables: real exports, real imports, real Gross Domestic Product (GDP), and price indices extracted directly from data sources such as the Central Bank, the World Bank and the IMF, with only real exchange rate volatility and Real Exchange Rate (RER) as derived data series. All data figures are expressed in Rupees millions, unless otherwise stated. A time series analysis was performed on exchange rate volatility and Sri Lanka’s Export Growth, involving Augmented Dickey Fuller (ADF) unit root test, Johansen Co-integration test, Vector Error Correction (VEC) modelling and Granger casualty tests. The study finds that there is a unique co-integrating vector linking real exports, relative export prices and real exchange rate volatility both in the short- and long-run. Further, the findings show that the volatility of the real exchange rate has a significant impact on exports destined to Sri Lanka’s main export markets, which are the USA and the UK, both in the short- and long-run. Overall, the findings of the study confirm the notion that Sri Lanka’s export trading activities could be expanded by maintaining a stable competitive Real Exchange Rate.
Keywords: Exchange Rate, volatility, exports, co-integration, vector error correction